Advances in Cellulose-Based Hydrogels - Demitri, Christian; Bonetti, Lorenzo; Riva, Laura (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This volume collects the recent progress in cellulose-based hydrogels, including gels prepared from natural cellulose and its derivatives, cellulose graft co-polymers, and composite gels based on cellulose, covering key aspects of cellulose-based hydrogels, including design, characterization, as well as application-focused research.